2021
DOI: 10.1016/j.apsb.2020.12.020
|View full text |Cite
|
Sign up to set email alerts
|

Clinical efficacies, underlying mechanisms and molecular targets of Chinese medicines for diabetic nephropathy treatment and management

Abstract: Diabetic nephropathy (DN) has been recognized as a severe complication of diabetes mellitus and a dominant pathogeny of end-stage kidney disease, which causes serious health problems and great financial burden to human society worldwide. Conventional strategies, such as renin-angiotensin-aldosterone system blockade, blood glucose level control, and bodyweight reduction, may not achieve satisfactory outcomes in many clinical practices for DN management. Notably, due to the multi-target function, Chinese medicin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
96
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 164 publications
(113 citation statements)
references
References 129 publications
1
96
0
Order By: Relevance
“…The results demonstrate that TS2HF was effective in the treatment of diabetic nephropathy in vivo when evaluated in rats with T2D nephropathy, similar to results of other TCM remedies. 10 These results are consistent with what is known about the effects of specific ingredients in the TS2HF mixture. According to traditional medicine theories, Astragalus mongholicus Bunge lowers blood glucose in type 1 and type 2 diabetes.…”
Section: Rat Kidney Histopathologysupporting
confidence: 89%
“…The results demonstrate that TS2HF was effective in the treatment of diabetic nephropathy in vivo when evaluated in rats with T2D nephropathy, similar to results of other TCM remedies. 10 These results are consistent with what is known about the effects of specific ingredients in the TS2HF mixture. According to traditional medicine theories, Astragalus mongholicus Bunge lowers blood glucose in type 1 and type 2 diabetes.…”
Section: Rat Kidney Histopathologysupporting
confidence: 89%
“…As the onset of DN is often asymptomatic in its early stages, many diabetic patients exhibit proteinuria and, in some cases, nephrotic syndrome [ 13 ], with a subset of these patients ultimately developing ESRD and requiring dialysis. DN thus imposes a major medical and economic burden on affected patients, their families, and society as a whole [ 5 ]. However, research efforts pertaining to DN are complex and multifaceted, necessitating a comprehensive systematic overview of this research space in order to effectively identify current trends and emerging hotspots in the field.…”
Section: Discussionmentioning
confidence: 99%
“…The pathogenesis of DN is characterized by basement membrane thickening and glomerular extracellular matrix accumulation [ 3 ], with proteinuria serving as one of the earliest clinical signs of this disease prior to its progression to ESRD [ 4 ]. To date, traditional diabetes-related therapies such as weight loss, glycemic control, and renin-angiotensin-aldosterone system (RAAS) inhibitor administration have failed to yield satisfactory clinical outcomes as a means of treating DN [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…28,29 For instance, TNF-α is a mononuclear macrophage pro-inflammatory factor, which is the earliest inflammatory factor to appear during the inflammatory response of the organism and it is elevated in patients with abnormal glucose tolerance. 30 Studies have shown that TNF-α also reduces the DNA binding activity of PPARγ, thereby inhibiting the expression of adiponectin mRNA, which in turn affects insulin signaling. 31 Our experimental results showed that prolonged feeding of the high-fat diet led to an expansion of adipocytes with severe inflammatory infiltration and significant positive expression of macrophage factors such as CD68 and CD11c in line with the literature description.…”
Section: Papermentioning
confidence: 99%